Greater Success of Primary Fascial Closure of the Open Abdomen: A Retrospective Study Analyzing Applied Surgical Techniques, Success of Fascial Closure, and Variables Affecting the Results. (June 2017) - Kääriäinen, M.; Kuuskeri, M.; Helminen, M.; Kuokkanen, H.
Background and Aims: The open abdomen technique is a standard procedure in the treatment of intra-abdominal catastrophe. Achieving primary abdominal closure within the initial hospitalization is a main objective. This study aimed to analyze the success of closure rate and the effect of negative pressure wound therapy, mesh-mediated medial traction, and component separation on the results. We present the treatment algorithm used in our institution in open abdomen situations based on these findings. Material and Methods: Open abdomen patients (n = 61) treated in Tampere University Hospital from May 2005 until October 2013 were included in the study. Patient characteristics, treatment prior to closure, closure technique, and results were retrospectively collected and analyzed. The first group included patients in whom direct or bridged fascial closure was achieved, and the second group included those in whom only the skin was closed or a free skin graft was used. Background variables and variables related to surgery were compared between groups. Results and Conclusion: Most of the open abdomen patients (72.1%) underwent fascial defect repair during the primary hospitalization, and 70.5% of them underwent direct fascial closure. Negative pressure wound therapy was used as a temporary closure method for 86.9% of the patients. Negative pressure wound therapy combined with mesh-mediated medial traction resulted in the shortest open abdomen time (p = 0.039) and the highest fascial repair rate (p = 0.000) compared to negative pressure wound therapy only or no negative pressure wound therapy. The component separation technique was used for 11 patients; direct fascial closure was achieved in 5 and fascial repair by bridging the defect with mesh was achieved in 6. A total of 8 of 37 (21.6%) patients with mesh repair had a mesh infection. The negative pressure wound therapy combined with mesh-mediated medial traction promotes definitive fascial closure with a high closure rate and a shortened open abdomen time. The component separation technique can be used to facilitate fascial repair but it does not guarantee direct fascial closure in open abdomen patients.